An Effective New Cryopreservation Procedure for Pancreatic Islets Using Hollow Fiber Vitrification - Nagaya, M.; Matsunari, H.; Kanai, T.; Maehara, M.; Nakano, K.; Umeki, I.; Katsumata, Y.; Kasai, Y.; Sakai, R.; Kobayashi, M.; Honda, M.; Abe, N.; Watanabe, M.; Umeyama, K.; Nagashima, H. (Hormone and Metabolic Research, 2016)
The present study aimed at establishing a new cryopreservation method for mouse pancreatic islets by vitrification using hollow fibers as a container. A unique feature of the hollow fiber vitrification (HFV) method is that this method achieves stable vitrification using a minimum volume of cryoprotectant (CPA) solution, thereby ensuring high viability of the islets. The cytotoxicity, optimum composition, and concentration of the CPAs for vitrifying islets were examined. The viability, functional-integrity of vitrified islets were evaluated in comparison with those vitrified by conventional methods. Insulin secretion was measured in vitro by a static incubation assay and the metabolic functions was tested after transplantation into Streptozotocin-induced diabetic mice. The combination of 15% dimethyl sulfoxide+15% ethylene glycol resulted in the best CPA solution for the HFV of islets. HFV showed the highest viability in comparison to 2 vitrification methods, open pulled straws and vitrification with EDT324 solution. The vitrified islets stably expressed β-cells markers NeuroD, Pancreatic and duodenal homeobox-1, and MafA. Transplantation of the vitrified islets achieved euglycemia of the host diabetic mice and response to an intraperitoneal glucose tolerance test to a similar extent as non-vitrified transplanted islets. The HFV method allows for efficient long-term cryopreservation of islets.
Keywords: islet transplantation; pancreatic islet; vitrification; cryopreservation; hollow fiber